Assessment and Characterization of Genetic Diversity In Lentil (Lens Culinaris Medik.) Through K-Means Clustering - Hussain , Syed Atiq; Iqbal, Muhammad Sajjad (Bangladesh Journal of Botany, 2022)
Lentil is a major legume crop that has much potential to combat malnutrition and food security but its yield is not sufficient due to less number of varieties available for diverse ecologies. To explore new generic lines, 220 genotypes of Pakistan, USA, Syria and unknown origin were characterized for agronomic traits viz., seed yield, harvest index, 100-seed weight, biological yield, plant height, lower pod height, pod size, seeds per pod, days to maturity, cooking time, number of hard seed and number of pods. K-means clustering revealed various component groups both in 2018 and 2019 with 5 clusters each. PC1 contributed 92.4% of variability while PC2 exhibited 4.1% for 2018, during 2019 PC1 90.53% and PC2 as 4%. Distance between class centroids exhibited maximum divergence group between clusters. Genotypes 6084 and 6122 (Pakistan) and 6062 (Syria) have been recommended for large scale cultivation on farmers field and breeding programs. Bangladesh J. Bot. 51(3): 597-605, 2022 (September)